Pemanfaatan Media Youtube Terhadap Kreativitas Belajar Peserta Didik Dalam Mata Pelajaran Pendidikan Pancasila Dan Kewarganegaraan - Rezet Putra; Yulita Pujilestari (JURNAL PENCAKAR (Pendidikan Pancasila dan Kewarganegaraan), 2026)
Proper use of social media by teachers can influence students' learning creativity. Teachers are required to be able to create good and enjoyable learning situations. One effort that teachers can make is to use social media as a stimulus for learning. YouTube is a medium for developing students' learning creativity in Pancasila and Citizenship Education subjects.This research aims to find out whether there is an effect of using YouTube media on student learning creativity in the subject of Citizenship Education. This type of research uses a quantitative approach with correlational methods. Student Learning Creativity in Internship Subjects (Y). This means that there is a significant influence between the use of Youtube social media on student learning creativity in PPKN subjects. Based on the results of testing the correlation coefficient between Utilization of Youtube SocialMedia on Student Learning Creativity in PPKN Subjects, it has a positive influence and direction, and is significant. This means that there is a very high relationship between Utilization of Youtube SocialMedia and Student Learning Creativity in Civic education